Incidência e evolução da polipose nasal em crianças e adolescentes com fibrose cística - Weber, Silke Anna Theresa [UNESP]; Ferrari, Giesela Fleischer [UNESP] (FapUNIFESP (SciELO), 2008)
Nasal polyps are a clinical sign of alert for investigating Cystic Fibrosis (CF). Aims: To study the incidence of nasal polyps in children and adolescents with cystic fibrosis, its possible association with age, gender, clinical manifestations, genotype and sweat chlorine level, and its evolution with topical steroid therapy. Methods: Clinical symptoms, sweat chlorine level and genotype were studied in 23 cystic fibrosis patients. Nasal polyps were diagnosed by nasal endoscopy and treated with topical steroids during 6 months, followed by a second nasal endoscopy. Fisher test was used for statistical analysis. Results: Nasal polyps were found in 39.1% of the patients (five bilateral, four unilateral), all older than six years, recurrent pneumonia in 82.6%, pancreatic insufficiency in 87% and malnutrition in 74%. No association was seen between nasal polyps and sweat chlorine level, genotype, clinical sings of severity and nasal symptoms. Seven patients improved in their nasal polyps with topical steroids, six showed complete resolution. Conclusion: The study showed a high incidence of nasal polyps in older children, who span the entire range of clinical severity, even in the absence of clinical nasal symptoms. Topical steroid therapy showed good results. An interaction among pediatricians and otolaryngologists is necessary for diagnosis and follow-up. 2008 © Revista Brasileira de Otorrinolaringologia. All Rights reserved.
Incidence and evolution of nasal polyps in children and adolescents with cystic fibrosis
Keywords: Cystic fibrosis; Diagnosis; Endoscopy; Polyposis; Therapy; chlorine; mometasone furoate; adolescent; adult; age; clinical article; cystic fibrosis; disease severity; endoscopy; Fisher exact test; follow up; gene mutation; genetic analysis; genotype; human; incidence; malnutrition; nose polyp; otorhinolaryngology; pancreas insufficiency; pneumonia; polyposis; school child; sex difference; steroid therapy